The effect of kinesio taping on lower back pain among obese housewives / Noramirah Samsikama - Samsikama, Noramirah (Faculty of Sport Science and Recreation, 2016)
The purpose of this study is to study 1he effect of kinesio taping on lower back pain among obese housewives. Apart from that, it also wants to determine 1he level of pain and disability index and also to measure physical activity level on experimental and control group. Population for 1he experimental group was from Indera Mahkota, Kuantan (n=15) and for control group from Felda Tersang, Raub (n=15). A total of 30 subjects (n=30) were selected via purposive random sampling participated in this study. Results showed 1hat 1here was no significant difference (p>0.05) in level of pain and disability index of ODI (p=.29), VAS (p=.27) and RMQ (p=.38). For the physical activity level there was also no significant difference (p>O.05) in the IPAQ (p=.27). the back functionality there was also no significance difference in lumbar flexion (p>O.05) but for 1he MST result there showed significant (p=O.OO). In conclusion, the findings in this study indicated that kinesio tape does not effective to increase back functioning but it was act as 1he medium of pain relief. There was an improvement when applying kinesio tape but there need to include exercise therapy during the intervention program to get a significant result.